Advanced Method for Evaluation of Gastric Cancer Risk By Serum Markers: Determination of True Low‐Risk Subjects for Gastric Neoplasm. Issue 1 (11th November 2013) - Boda, Tomoyuki; Ito, Masanori; Yoshihara, Masaharu; Kitamura, Yoko; Matsuo, Taiji; Oka, Shiro; Tanaka, Shinji; Chayama, Kazuaki
Abstract Background Patients with negative anti‐Helicobacter pylori antibody titer and high pepsinogen (PG) level (group A) are regarded as having a low risk for gastric cancer. However, gastric cancer cases are occasionally observed in this group. We aimed to elucidate the clinical features of gastric neoplasm in group A patients and reviewed advanced methods for mass screening. Materials and Methods A total of 271 gastric epithelial neoplasm patients were enrolled. We classified them according to the H. pylori‐PG system and determined the number of patients in each group. After excluding true H. pylori‐negative cases from group A (group A'), we examined the differences between group A' and group non‐A. Results Group A included 30 (11%) patients, and only three of these were true negative for H. pylori. All patients in group A' (n = 27) exhibited endoscopic atrophy in the gastric corpus. Serologically, these patients showed low gastrin, low PG II and high PG I/II ratio, indicative of post‐eradication. Histologically, 24 (89%) of these had little inflammation, and 26 (96%) were negative for H. pylori by immunohistochemistry. No difference was observed in the incidence of metachronous gastric tumors between group A' and group non‐A. The discriminant function using gastrin and PGs could distinguish these 27 patients from true H. pylori‐negative controls with 85% sensitivity and 84% specificity. Conclusions Group A included a certain number of patients with atrophic gastritis who were potentially at risk of gastric neoplasm development. Although evaluation of corpus atrophy is necessary for the identification of these patients, the discriminant function may be useful.